Sistem Informasi Perizinan SIUP & SITU Pada Kantor PTSA Kota Bandar Lampung Berbasis Web - Anggi Andriyadi; Syela Angreani (Jurnal SIMADA (Sistem Informasi dan Manajemen Basis Data), 2018)
Licensing is legality granting to the particular person or company, whether it’s granted in Licensed or Business Registration Certificate. License could be interpreted as dispensation or exemption from prohibition to established a particular business, therefore it could provide legal juristical, protecting from unfair competition which a commitment of obeying the law. Currently, Licensing is running conventionally, therefore on One-Stop Service office in Bandar Lampung is experiencing difficulties on licensing process, which are all documentation and licensing data are in Hardcopy files. The registrants should coming early and waiting in line, which causing a time waste. This system is designed to help providing an information of SIUP and SITU which based on website. This research is using waterfall method, with the stages are Analysis, Design, Coding and Testing. The results from this research is able to show the data of registrant, approval notice, rejection notice, and digital business registration certificate that could downloaded online. Keywords: Licencsing; SIUP; SITU and Web